Pengaruh Penyuluhan Berbasis Virtual Reality terhadap Pengetahuan Pencegahan Kanker Payudara pada Remaja - Kurnia Rahma Syarif; Masdiana AR; Muhammad Rezky (Journal of Innovation Research and Knowledge, 2026)
Breast cancer education from adolescence is important for building early awareness of risk factors, warning signs, and preventive behavior. This study examined the effect of virtual reality (VR)-based health education on adolescents' knowledge of breast cancer prevention. A quantitative pre-experimental one-group pretest-posttest design was conducted at the Department of Nursing, Poltekkes Kemenkes Makassar, from March to August 2026. Twenty first- and second-year students aged 17–20 years participated. Knowledge was measured using a closed-ended questionnaire before and after a VR education session. Descriptive statistics summarized participant characteristics and knowledge categories, while a paired t-test assessed the difference in mean scores. Before the intervention, 55.0% of participants had poor knowledge, 40.0% had moderate knowledge, and 5.0% had good knowledge. After the intervention, 95.0% had good knowledge and 5.0% had moderate knowledge. The mean score increased from 54.50 ± 11.46 to 87.50 ± 8.51, a mean difference of 33.00 points (p < 0.001). VR-based education was associated with a significant improvement in breast cancer prevention knowledge. However, controlled studies with larger samples and follow-up measurements are required to establish causal effects and knowledge retention.